1986
DOI: 10.1007/bf01299814
|View full text |Cite
|
Sign up to set email alerts
|

Experimental disease in infant goats induced by aMycobacterium isolated from a patient with Crohn's disease

Abstract: Pilot studies were done to assess the pathogenicity of a Mycobacterium which had been recovered from the diseased ileum of a patient with Crohn's disease. In four separate studies, pairs of infant goats served as subjects. One of each pair received an oral inoculum of freshly harvested Mycobacterium species strain Linda suspended in cream. A littermate or stablemate which received only cream served as control. Necropsies were done at three, five, six, and 10 months postinoculation. Each of the four inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
9

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 32 publications
3
42
0
9
Order By: Relevance
“…Later subsequent studies demonstrated that the isolates were genetically identical to strains of M. paratuberculosis originated from cattle, and were able to develop paratuberculosis after oral administration to infant goats (Van Kruiningen et al, 1986). Similar isolation of the organism from Crohn's disease patients was described by Chiodini (1989), Pavlík et al (1994), and Thompson (1994).…”
Section: A Possible Role In Crohn's Diseasesupporting
confidence: 54%
“…Later subsequent studies demonstrated that the isolates were genetically identical to strains of M. paratuberculosis originated from cattle, and were able to develop paratuberculosis after oral administration to infant goats (Van Kruiningen et al, 1986). Similar isolation of the organism from Crohn's disease patients was described by Chiodini (1989), Pavlík et al (1994), and Thompson (1994).…”
Section: A Possible Role In Crohn's Diseasesupporting
confidence: 54%
“…Animals may shed M. avium subsp. paratuberculosis in their milk, even during subclinical infection (12,25), and human exposure to M. avium subsp. paratuberculosis through dairy products has become an issue of concern, despite the fact that there is no conclusive evidence to support association of this pathogen with Crohn's disease (9,10).…”
mentioning
confidence: 99%
“…A role for bacterial antigens in the development of the disease was suggested [ 12,13]. Slow growing strains of Mycobacterium have been impli cated for the pathogenesis of CD [14][15][16], recently supported by a study of Gitnick et al [17]. Two other studies, however, did not confirm this view [18,19].…”
Section: Discussionmentioning
confidence: 99%